Comparative characteristic of the brain natriuretic peptide and angiotensin II expression index in the structure of locus coeruleus of brain stem in rats with arterial hypertension of various origins - M. V. Danukalo; O. V. Hancheva; Ye. V. Kadzharian (Zaporozhye State Medical University, 2019)
The aim of our study was to determine the characteristics of the BNP and AT II expression in the LC structure of rat brain stem with experimental (genetically determined essential and secondary endocrine-salt) arterial hypertension and to give a comparative description of the expression pattern of these peptides in etiologically different types of arterial hypertension. Materials and methods. The study was carried out on adult 30 male rats. 20 Wistar animals were divided into two groups - control (10 rats) and 10 rats with simulated endocrine-salt AH (ESAH) and 10 rats of the SHR line with essential AH (EAH). The expression parameters of neuropeptides, such as the content, concentration, and relative area of the immunoreactive material, were studied using an immunohistochemical method. Results. It was found that from all BNP expression parameters in the locus coeruleus structure, only relative area increased significantly in both groups. The concentration did not significantly change, and the content of immunoreactive material increased significantly only in animals with ESAH. At the same time, all parameters of angiotensin II expression increased significantly in both experimental groups. Thus, in rats with experimental arterial hypertension in the locus coeruleus structure, more pronounced changes in expression parameters are characteristic for angiotensin II, rather than for BNP. There is a discrepancy between levels of pressor angiotensin II expression and depressor BNP expression in the direction of angiotensin II expression increasing during the arterial hypertension formation. The nature and peculiarities of these neuropeptides expression in the LC structure depend on the key link of the pathogenesis of the modeled arterial hypertension. Conclusions. In rats of the control group with normal blood pressure in LC structure, AT II is more represented. The content and concentration of IRM to AT II are 2.32 and 2.19 times higher than the corresponding BNP values. Prevalence of AT II in the LC structure of the brainstem remains even when arterial hypertension is formed, regardless of its etiology. However, the etiopathogenetic mechanisms of arterial hypertension development impose their own characteristics. In EAH, the content and concentration of AT II is higher than BNP by 4.58 and 3.59 times; in ESAH - by 2.16 and 2.83 times. In the pathogenesis of essential arterial hypertension formation an important role is played by a change in the central control of blood pressure regulation. It is characterized by a significant predominance of the pressor component AT II over the depressor BNP in the brainstem LC structure.